2012
DOI: 10.1007/s12665-012-1738-4
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on the swelling pressure and saturated hydraulic conductivity of the compacted GMZ01 bentonite

Abstract: International audienceUsing a newly developed apparatus, swelling pressure tests and saturated hydraulic conductivity tests on the compacted Gao-Miao-Zi (GMZ01) bentonite with an initial dry density of 1.7 Mg/m(3) were conducted at various temperatures. Based on the test results, the mechanisms of influence of temperature on the swelling pressure and saturated hydraulic conductivity were analyzed. Results indicate that swelling pressure increases with the increase in temperature. The swelling pressures measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(35 citation statements)
references
References 21 publications
6
29
0
Order By: Relevance
“…The shape of the swelling pressure evolution curve was characterized by these two peaks (Fig. 7) and was in accordance with results achieved in similar studies using GMZ bentonite ( [70,68]) and FEBEX bentonite ( [71]). …”
Section: Influences Of Alkaline Solutionssupporting
confidence: 89%
“…The shape of the swelling pressure evolution curve was characterized by these two peaks (Fig. 7) and was in accordance with results achieved in similar studies using GMZ bentonite ( [70,68]) and FEBEX bentonite ( [71]). …”
Section: Influences Of Alkaline Solutionssupporting
confidence: 89%
“…Furthermore, the swelling pressure significantly depends on the type of water the bentonite is exposed to (Karnland, 1997;Xie et al, 2007;Karnland et al, 2007;Herbert et al, 2008;Lee et al, 2012). Lloret (2004, 2008) and Lee et al (2010) reported decreasing swelling pressure with increasing temperature while Shirazi et al (2010) and Ye et al (2013) found increasing swelling pressure with increasing temperature. Birgersson et al (2010) reported on a theoretical relation of the swelling pressure on the temperature and could prove and calculate a marked drop of the swelling pressure upon freezing.…”
Section: Introductionmentioning
confidence: 99%
“…where K sat is the saturated hydraulic conductivity (cm/s), Q is the quantity of water (cm 3 ), A is the cross-sectional area perpendicular to flow (cm 2 ), t is the time (s) required for Q to be discharged, i is hydraulic gradient, h is the head difference between the top and the bottom of the soil specimen (cm), and L is length of the seepage path (i.e., the height of the sample) (cm). The influence of temperature on saturated permeability cannot be neglected [6,[34][35][36]; therefore, the test apparatus was placed in an SHH-C3000 constant temperature controller (China) with a range of 0-60 • C and an accuracy of 0.1 • C. In this study, 20 • C was set as the standard temperature to avoid the correction of K sat [37]. Moreover, the hydraulic gradient was set to 3 to ensure sufficient discharge for the water chemical analysis.…”
Section: K Sat Measurementmentioning
confidence: 99%